Rekomendasi Tempat Wisata Menggunakan Metode TOPSIS Pada Dinas Kebudayaan Dan Pariwisata Kota Gorontalo - Syaifuddin; M Salim; Hamka Witri Kamase (Bulletin of Computer Science Research, 2022)
Decision-making is experienced by the Tourism Office, which must make recommendations for tourist attractions in Gorontalo Province. Decision-making that combines quantitative and qualitative elements can be assisted by a decision support system (SPK). According to its understanding, SPK is an interactive computer-based system that helps decision-makers use data and various models to solve unstructured problems. This subjectivity usually occurs to reduce the complexity of the decision-making process due to many alternatives. If in the decision-making process for tourist attraction recommendations, users can be assisted by a computerized decision support system that provides desired recommendations for tourist attractions. To calculate the consideration of this tourist attraction in the decision support system can use the topsis method with criteria such as Tourist cost, Time of visit, Age, Type of attraction, Mileage, Facilities, Beauty, and Safety. The method used in this study is the TOPSIS Method because it is based on its concept that the best alternative has the shortest distance from the positive ideal solution and the longest distance from the Negative ideal solution.